THE SUCCESSES OR FAILURES OF CONFIDENCE BUILDING MEASURES: GEOPOLITICAL DYNAMICS IN SUDAN-SOUTH SUDAN - Oktaviani Yashinta, Friska; Pedrason, Rodon; Ferdinand Wenas Inkiriwang, Frega (Universitas Muhammadiyah Tapanuli Selatan, 2024)
Competition between Sudan and South Sudan for valuable resources, particularly oil, has been the main cause of their protracted conflict. The conflict over these, has contributed to the already unstable relations between the two nations, resulting in prolonged conflicts over the control of these resources. The pursuit of economic and geopolitical supremacy, specifically in relation to valuable oil reserves, has consistently fueled animosity between the two nations. The secession of South Sudan from Sudan has exacerbated conflicts, particularly regarding the resource-rich Abyei region, posing a significant obstacle. The objective of this study is to analyze the effectiveness of confidence-building measures (CBMs) in resolving conflicts resulting from resource competition between two countries. This research utilizes a qualitative methodology and relies on secondary data acquired from diverse sources, such as books, journals, and online platforms. The data selection was predicated on its relevance to the research objectives. The study presents insights into confidence-building measures implemented in Sudan and South Sudan, exploring the factors contributing to the success or failure of these measures. Additionally, it delves into the geopolitical dynamics that influence the effectiveness of CBMs between two countries.